2021
DOI: 10.1161/circresaha.120.318234
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Imaging at Ryanodine Receptors Reveals β 2 -Adrenoceptor Driven Arrhythmias

Abstract: Rationale: 3',5'-cyclic adenosine monophosphate (cAMP) is a ubiquitous second messenger which, upon β-adrenergic receptor (β-AR) stimulation, acts in microdomains to regulate cardiac excitation-contraction coupling by activating phosphorylation of calcium handling proteins. One crucial microdomain is in vicinity of the cardiac ryanodine receptor type 2 (RyR2) which is associated with arrhythmogenic diastolic calcium leak from the sarcoplasmic reticulum (SR) often occurring in heart failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…FRET measurements were performed on human atrial myocytes 48 h after transduction with the adenovirus encoding Epac1-camps [ 18 ], pm-Epac1 [ 19 ] and Epac1-JNC [ 20 ]. A K + -Ringer solution containing: 144 mM NaCl, 5.4 mM KCl, 1 mM MgCl 2 , 1 mM CaCl 2 , 10 mM HEPES, adjusted to 7.4 pH with NaOH at room temperature (RT) was used to maintain cells, and images were taken every 5 s. The FRET system used consisted of a standard inverted microscope (Leica DMI3000, Leica Biosystems, Wetzlar, Germany) with a 63×/1.4 oil immersion objective, an LED light source (pE-100, CoolLED), a beam splitter (DV2, Photometrics, Birmingham, UK), and a camera (CMOS camera optiMOS, Photometrics, Birmingham, UK).…”
Section: Methodsmentioning
confidence: 99%
“…FRET measurements were performed on human atrial myocytes 48 h after transduction with the adenovirus encoding Epac1-camps [ 18 ], pm-Epac1 [ 19 ] and Epac1-JNC [ 20 ]. A K + -Ringer solution containing: 144 mM NaCl, 5.4 mM KCl, 1 mM MgCl 2 , 1 mM CaCl 2 , 10 mM HEPES, adjusted to 7.4 pH with NaOH at room temperature (RT) was used to maintain cells, and images were taken every 5 s. The FRET system used consisted of a standard inverted microscope (Leica DMI3000, Leica Biosystems, Wetzlar, Germany) with a 63×/1.4 oil immersion objective, an LED light source (pE-100, CoolLED), a beam splitter (DV2, Photometrics, Birmingham, UK), and a camera (CMOS camera optiMOS, Photometrics, Birmingham, UK).…”
Section: Methodsmentioning
confidence: 99%
“…As is well-known, the accumulation of Ca 2+ in the cytoplasm may result in delayed afterdepolarizations, which can trigger arrhythmia. Considering the increased occurrence of Ca 2+ sparks in HL-1 cardiomyocytes treated with 512 µM aminophylline ( Figure 6 ), the concentration-independent “stochastic” effect of aminophylline observed in our study may be a consequence of microdomain cAMP level–related diastolic release of Ca 2+ via independent clusters of RyR2 receptors ( Berisha et al, 2021 ). Such transient Ca 2+ accumulation may induce an increased BR and, following Ca 2+ depletion, results in a pause in the investigated cardiac cell’s beating clusters.…”
Section: Discussionmentioning
confidence: 65%
“…The ADRB2 gene encodes the β2-adrenergic receptor. Researchers have found that ADRB2 strongly increases localized RyR2-related cAMP levels during the over-activation of the SNS associated with cardiac hypertrophy or HF and increases ventricular arrhythmias ( 30 ). The ADRB2 also increases infiltration by pro-inflammatory macrophages, induces the production of IL-18, and sequentially stimulates the expression of connexin43 (Cx43) in fibroblasts in a paracrine manner, resulting in gap junction remodeling, myocardial fibrosis, and deterioration of cardiac function ( 31 ).…”
Section: Discussionmentioning
confidence: 99%